ANALISIS KONSEP PENDIDIKAN AKHLAK DALAM KITAB WASHOYA AL ABA LIL ABNA KARYA MUHAMMAD SYAKIR AL ISKANDARI - Zainudin, Udin; Ayi Sya‟adah Staniah (HASBUNA : Jurnal Pendidikan Islam, 2024)
This research aims to analyze the concept of moral education contained in the book Washoya al Aba Lil Abna by Muhammad Syakir Al Iskandari. The research method used is library research, which involves collecting and analyzing data from various related library sources. The book Washoya al Aba Lil Abna was chosen as the object of study because it contains moral and ethical advice that is important for character formation in the younger generation. The research results show that moral education in this book emphasizes the values of honesty, simplicity, respect for parents and social responsibility. The author also emphasizes the importance of example and real practice in daily life to instill moral values in children. This research concludes that the concept of moral education promoted by Muhammad Syakir Al Iskandari is relevant and applicable in the context of modern education, and can be a reference for educators and parents in guiding children towards noble morals.